Fifth annual report - Mew, E. B. ; Miller, Mary F. ; Norman, E. M. ; Roberts, D. ; Galbraith, H. ; Worden, M. ; Daukes, A. ; Waterworth, E. M. ; Mottram, D. B.; Capener, Norman (1932)
1932 1932 1930s 86 pages : illustrations TRAINING AND WELFARE DEPARTMENT. Hon. Sec. : MRS. JOHN RADCLIFFE. Assist. Sec. : MISS BYRNE. Industry Instructress : Miss VAUGHAN. 150 cases have passed through the department during the year and help and advice has been given to each. The considerable increase in the adult cases attending the various Clinics, with the addition of the three new Clinics, has resulted in increased work in the department, as for most of these cases, other than Tubercular who need treatment or appliances, funds have to be collected from various sources to enable these to be provided. Employment Advisory Committee. The Committee has had a difficult task this year ; owing to the general depression it has been almost impossible to place cripples in work. The usual reply to a request for such help being that the employer is decreasing his staff ; nevertheless the members of the Employment Committee have shown as much keenness as ever, and their advice has been most useful. Home Industry. A great increase in application for admission has been experienced this year, resulting in 22 new workers being taken on. To assist the Instructress in her difficult task of teaching and supervising, the General Purposes Committee authorised the purchase of a car, thus enabling her to get about the county more expeditiously. Sales have decreased by £24/9/1, which, considering the universal depression, appears satisfactory. In November Miss Geen generously offered her services in running a shop if such could be found, and a small one in Southernhay East was discovered and let let to D.A.C.A. at the nominal rent of £1 per week. It was fitted up by the kindness of Miss Geen and other friends. Since its opening it has helped considerably in keeping the stock within reasonable proportions, in procuring orders, and in advertising not only the work of the Home Industry but that of D.A.C.A. as a whole. In considering the decrease in sales during the year, it should be remembered that the shop has not been opened sufficiently long to alter materially the 31 292/841.51/2/2